Estudio del comportamiento del turista millenial y su influencia en las tendencias turísticas en la ciudad de Guayaquil - Triviño Márquez, Steeven Daniel (2025)
This study skees to understand how Young travelers influence trends in Guayaquil they like real, ecological experiences full of technology, a great opportunity to promote local Development. We use mixed methods: numbers (quantitative) and stories (qualitative). We surveyed 50 people, including millennial travelers and locals related to the sector. The results say that although Guayaquil has the potential to attract them, it must improve its digital and internet technology and also promote itself better online. We recommend creating packages to suit the millennial taste: interesting digital things or green cultural events all highlight what is special about the city.